2014
DOI: 10.1016/j.jtcvs.2013.12.055
|View full text |Cite
|
Sign up to set email alerts
|

Mapping-guided total excision of the sinoatrial node for inappropriate sinus tachycardia

Abstract: heart syndrome, with 98% of patients demonstrating a neoaortic dilation with a z score greater than 2 at a median of 9.2 years of follow-up. 5 The etiology of neoaortic aneurysm formation may involve myxoid degeneration as opposed to atherosclerosis 3 ; however, it is unclear whether any contributing factors exist (eg, hypertension, hyperlipidemia, smoking status, pregnancy) and whether medical therapy can mitigate them.Given that the rate of aneurysmal growth of the neoaorta appears unpredictable and smaller … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…This lesion resolved the patient’s tachycardia and replaced it with a stable junctional escape rhythm. 21 Similar techniques used to completely isolate the SA node were reported in case reports 22,23 and a case series by Hendry and colleagues 24 Both case reports noted symptomatic relief and freedom from medications up to 1 year postoperatively, 22,23 whereas Hendry and colleagues 24 reported that 1 of 3 patients in their series with sinus tachycardia was in sinus rhythm several years postoperatively. With the advent of ablation technology, cryoablation and bipolar RF energy are used to avoid surgical incisions, shorten the operative time, and avoid cardiopulmonary bypass.…”
Section: Commentmentioning
confidence: 78%
“…This lesion resolved the patient’s tachycardia and replaced it with a stable junctional escape rhythm. 21 Similar techniques used to completely isolate the SA node were reported in case reports 22,23 and a case series by Hendry and colleagues 24 Both case reports noted symptomatic relief and freedom from medications up to 1 year postoperatively, 22,23 whereas Hendry and colleagues 24 reported that 1 of 3 patients in their series with sinus tachycardia was in sinus rhythm several years postoperatively. With the advent of ablation technology, cryoablation and bipolar RF energy are used to avoid surgical incisions, shorten the operative time, and avoid cardiopulmonary bypass.…”
Section: Commentmentioning
confidence: 78%